Validade e eficácia da assinatura digital em contratos Eletrônicos: uma análise da manifestação de vontade no ambiente virtual. - Carneiro Leão Sobrinho, Haroldo (2024)
This dissertation investigates the validity and effectiveness of electronic signatures in digital consumer contracts, emphasizing the need for legal security and the functional equivalence with traditional signatures. It revealed that, although there is a growing legal recognition of digital signatures, there still are significant gaps in consumer protection, especially regarding data privacy and access to technology. The need for legislative updates to fully address the challenges of will manifestation and consent defects in the digital environment was identified. The research highlights the importance of an adaptive and updated regulatory framework, capable of facing the challenges brought by technological evolution, offering guidelines for future discussions on the intersection between law, technology, and consumer protection.